The relationship of hypertension with obesity and obstructive sleep apnea in adolescents. Issue 4 (18th February 2020) - Khan, Masrur A.; Mathur, Kanika; Barraza, Giselle; Sin, Sanghun; Yang, Christina J.; Arens, Raanan; Sutton, Nicole; Mahgerefteh, Joseph
Abstract: Objectives: To assess the independent relationships of obesity and obstructive sleep apnea (OSA) with hypertension/elevated blood pressure (EBP) in adolescent patients. Study Design: A retrospective cohort analysis was performed on 501 patients (age 13‐21 years) with three separate blood pressure measurements within 6 months of polysomnography. EBP was defined as average systolic blood pressure (SBP) ≤120 mm Hg; obesity as body mass index Z ‐score ≤1.65; and OSA as obstructive apnea‐hypopnea index <1. Pearson correlations and multivariable analyses were performed to assess the independent effects of the apnea‐hypopnea index and body mass index Z ‐score on SBP. Results: Of 501 patients (mean age 16 ± 2 years), 246 (49%) were male. OSA was present in 329 (66%) patients, obesity in 337 (67%), and EBP in 262 (52%). EBP was present in 70% of obese adolescents and 60% of adolescents with OSA. Univariable correlation showed a significant relationship between SBP, body mass index Z ‐score, and apnea‐hypopnea index. Multivariable linear regression analysis showed blood pressure was significantly associated with body mass index Z ‐score ( β  = .46; P  < .01), age ( β  = .25; P  < .01), and height Z ‐score ( β  = .14; P  < .01), but not apnea‐hypopnea index ( β  = .01; P  = .72). Conclusions: The relationship between OSA and EBP in adolescents is most closely associated with the degree of obesity. Further studies are needed to assess the effect of the treatment of obesity and OSA on blood pressure in adolescents.